Gene Therapy Death Prompts Review of Adenovirus Vector - Marshall, Eliot (Science (American Association for the Advancement of Science), 1999)
The impact of the death of Jesse Gelsinger on research into gene therapy is discussed. Gelsinger, a relatively fit 18-year-old with an inherited enzyme deficiency, died on Sep 17, 4 days after doctors injected a genetically altered virus into his liver.